2011 8th International Workshop on the Design of Reliable Communication Networks (DRCN) 2011
DOI: 10.1109/drcn.2011.6076900
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive approach to network resilience: Evolving challenge detection and mitigation

Abstract: It is widely agreed that computer networks need to become more resilient to a range of challenges that can seriously impact their normal operation. Challenges include malicious attacks, misconfigurations, accidental faults and operational overloads. As part of an overall strategy for network resilience, a crucial requirement is the identification of challenges in real-time, followed by the application of appropriate remedial action. In this paper, we motivate and describe a novel solution that enables the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Despite the multitude of mechanisms and techniques available, it is often not clear how these should be combined and coordinated in complex multi-service networks. We found that the published state-of-the-art in challenge detection and classification varies in the resources that are required, the timeliness and accuracy of their operation, and the challenges they can effectively operate with [12]. For example, localised detection in fluctuations of traffic volumes can give a rapid and relatively lightweight indication of the onset of challenges, such as DDoS attacks or flash crowd events, whereas a sophisticated classification system can yield more accurate information about the challenge, e.g., the identification of malicious flows, over a longer period of time.…”
Section: A Network Resiliencementioning
confidence: 97%
“…Despite the multitude of mechanisms and techniques available, it is often not clear how these should be combined and coordinated in complex multi-service networks. We found that the published state-of-the-art in challenge detection and classification varies in the resources that are required, the timeliness and accuracy of their operation, and the challenges they can effectively operate with [12]. For example, localised detection in fluctuations of traffic volumes can give a rapid and relatively lightweight indication of the onset of challenges, such as DDoS attacks or flash crowd events, whereas a sophisticated classification system can yield more accurate information about the challenge, e.g., the identification of malicious flows, over a longer period of time.…”
Section: A Network Resiliencementioning
confidence: 97%
“…The legitimate network traffics have the regular packet sizes from regular IP addresses on regular flow rates so that the entropy values are concentrated. The burst value of entropy represents the abnormal change of network traffics that leads detection of DDoS attack whenever it occurred [3] [4].…”
Section: Related Workmentioning
confidence: 99%
“…As shown in previous work [5], [6], [7] it is possible to adopt the behaviour of a system without the need to re-design and develop any of the functionality, and changes can be applied without the need to bring system to halt which is crucial for critical service point of view. However, there is still need to apply basic of policy refinement principals for autonomic management in cloud computing.…”
Section: Fig 1: Policy Refinement Stagesmentioning
confidence: 99%